THREE-DIMENSIONAL ORGANIZATION OF CONCLUSION CHANNELS AND ARTERIAL OF THE CIRCULATORY SYSTEM RIVER-BED OF INTACT PANCREAS OF MAN - Sherstyuk О.А.; Dubinin, S.I.; Tikhonova, O.A.; Tarasenko, Y.A.; Deynega, T.F.; Svincickaya, N.L.; Ulanovska-Gyba, N.A.; Katsenko, A.L. (World of Medicine and Biology, 2013)
To one of issues of the day there is research of three-dimensional organization and mutual relations of tubular structures of glands in morphology. Research was conducted on preparations of intact pancreas of man by the injection of vessels and excretory ducts by an acryl plats. On corrosive preparations three-dimensional organization of vascular rate and excretory ducts and their intercommunication is investigational.